Development of A Physics-Based E-Module Iman Taqwa-Loading CTL on Dynamic Fluid Materials - Siti Nurhafizah Adha; Fitri Nur Hikmah; Eko Wahyu Nur Sofianto (Universitas Lambung Mangkurat, 2024)
The CTL model is a model that can help teachers motivate students to make connections between the content of the material and real-life situations, and this model requires teachers to create alternative teaching materials as a guide. The development of good teaching materials that combine religious values with science. Therefore, researchers are interested in developing this e-module. This research aims to determine the validity of the product being developed, namely a physics e-module based on CTL containing implications for dynamic fluid material, and to find out how students respond to the product the researcher developed. This research is development research, and the development model used is the ADDIE development model, which consists of five stages. However, this research only reached the development stage because research aimed to develop and produce valid teaching materials based on validator assessments, and at each stage of this model, there is evaluation and revision. First, the researchers analyzed the curriculum, needs, and materials. Then, they design it, the initial design stage for developing a product. Next, the development is the stage where the previously prepared design realizes the product design. Validators consist of two physics lecturers and one physics teacher. The development trial subjects were 34 class XII, IPA 1, MAN 1, and HST students. The product validation results from material experts were 81%, and from media experts were 82%, where both of these figures are included in the very valid criteria. The results of the student response test on the product being developed were 85%, which met very good criteria. Based on these results, the physics e-module based on CTL contains imprints on dynamic fluid material is declared valid and very good. Implications development is helping teach physics in religion and dynamic fluid materials. Implications of research for helping increase learning module fluid dynamics include religion (Islamic).